Konstruksi Habitus Religius Siswa Sekolah Dasar di Tengah Dominasi Budaya Kunsumerisme: Studi di SD Negeri 2 Selabaya - Annisah Dwi Hastuti; M. Hanif (CV. ITTC INDONESIA, 2026)
The fast-growing influence of digital technology and social networking platforms has brought remarkable changes to the lives of elementary school children. Various internet trends now shape the way students think, behave, and live their daily routines. This situation becomes a challenge for schools in strengthening religious values among young learners. This study discusses the formation of students’ religious habitus at SD Negeri 2 Selabaya in the midst of an increasingly dominant consumerist culture. Using a qualitative approach involving observation, interviews, and documentation, the study reveals that the school promotes religious character through group prayers, chanting Asmaul Husna, Islamic learning activities, religious celebrations, and the practice of discipline and respectful behavior. Even so, social media still strongly affects students, especially in their enthusiasm for viral trends and modern popular culture. Consequently, cooperation between schools and parents is essential in reinforcing children’s religious character development.